(untitled) (Revista Electrónica Calidad en la Educación Superior, 2017)
En el presente artículo se muestra la opinión de directores y tesistas sobre algunos factores de la dinámica de trabajo, que se genera en la elaboración del trabajo final de graduación (TFG), de la Licenciatura en la Enseñanza de las Ciencias, donde cada director con su tesista forma un equipo virtual. Los proyectos o TFG de este programa pretenden ser una solución a problemáticas que corresponden a la comunidad interna o externa de una institución educativa para el mejoramiento de la educación científica. DIRECTORS AND THESIS CANDIDATES OPINION ON THE DYNAMICS OF THE FINAL GRADUATION WORK DEVELOPMENT IN THE SCIENCE TEACHING LICENTIATIE IN THE UNED Abstract The present article shows the opinion of Principals and theses on some factors of the work dynamics, which is generated in the elaboration of the final graduation work (FGW), of the Degree in the Teaching of Sciences, where each Principal with his thesis students forms a virtual team. The projects or FGW of this program pretend to be a solution to problems that correspond to the internal or external community of an educational institution, for the improvement of scientific education. Keywords: virtual team; principal; virtual system; education; investigator; natural science teaching